Interleukin-31 as a Clinical Target for Pruritus Treatment - Kabashima, Kenji; Irie, Hiroyuki (Frontiers in Medicine, 2021)
In recent years, the published literature has suggested the key involvement of the cytokine interleukin-31 (IL-31) in the symptomatology of pruritus, and both IL-31 and its receptor have become potential therapeutic targets for a range of pruritic diseases. Elevated levels of IL-31 or its receptor have been reported in the tissue or serum of patients with pruritic skin diseases, such as atopic dermatitis, prurigo nodularis, and psoriasis. Pruritus places a heavy burden on patients, and can have a negative impact on daily life, sleep, and mental health. Since current anti-pruritic treatments are often ineffective, affected patients are in urgent need of new therapies. As a result, drug development targeting the IL-31 pathway is evolving rapidly. To date, only nemolizumab, a humanized monoclonal antibody targeting the IL-31 receptor, has successfully completed late-stage clinical studies. This article will highlight our current clinical understanding of the role of IL-31 in pruritic disease, and explore recent progress in drug development as well as the anticipated future advances in this field.